Implementation of a High Power Quality BLDC Motor Drive Using Bridgeless DC to DC Converter with Fuzzy Logic Controller - Gopan K., V.; Shree, J. D. (Engineering, Technology & Applied Science Research, 2022)
Electric motor drives based on electronic power converters having good power quality parameters are getting huge acceptance. Conventional Diode Bridge Rectifier (DBR) and DC to DC converter-based methods have become obsolete, as they provide low power quality indices which hamper the supply by introducing current harmonics and conduction losses. Although there are many developments in motors and control strategies, the risk and complexity of such drives become bottlenecks in implementation. This study implemented a drive scheme with a brushless DC Motor. The new improved bridgeless topology was modified with an advanced fuzzy logic controller to further improve its power quality and performance. Due to low power, a high-speed application of Brush Less (BLDC) motor was selected for the drive scheme. This combination could achieve almost Unity Power Factor (UPF) and significantly improve control compared to conventional topologies. A circuit-wise analysis was conducted to design the converter’s components. The modifications were elaborated through mathematical expressions, and the parameters of power quality were analyzed and validated.